SENYAWA INHIBITOR α-GLUKOSIDASE DAN ANTIOKSIDAN DARI KUMIS KUCING DENGAN PENDEKATAN METABOLOMIK BERBASIS FTIR - Juliani -; Nancy D. Yuliana; Slamet Budijanto; C. Hanny Wijaya; Alfi Khatib (Jurnal Teknologi dan Industri Pangan, 2016)
Plant is well known as an excellent source for bioactive compounds. Metabolomics was reported as a potential tool to accelerate plant acitive compounds identification. In this research, FTIR-based metabolomics method was used to identify active compounds with α-glucosidase inhibitory and antioxidant activity in aerial parts of Orthosiphon stamineus (OS) extract and its fractions. Chemical profile of OS methanolic extracts and hexane, chloroform, butanol, and water fractions were analyzed using infrared spectroscopy. OS extracts and fractions showed inhibitory activity against α-glucosidase enzymes with IC50 value 154.07±30.60-465.83±85.34 µg/mL and antioxidant activity with IC50 value 7.41±0.02-19.35±0.09 µg/mL. Butanol fraction was the fraction with the highest α-glucosidase inhibitory activity and moderate antioxidant activity with IC50 value between 154.07±30.60 µg/mL and 10.84±0.54 µg/mL, respectively. The correlation between the biological activity and chemical composition data were analyzed using Orthogonal Projections to Latent Structures (OPLS). Based on the VIP (variable influence on projection), the coefficient value of the respective OPLS models, and IR database of compounds previously identified in OS, it was suggested that methoxy flavonoid (sinensitin and 5,6,7,3’-tetramethoxy-4’-hydroxy-8-C-preny-lflavone), diterpenes (orthosiphols, orthoarisins, neoorthosiphols, staminols, and staminolactones) and triterpenes (ursolic acid, oleanolic acid, betulinic acid, hydroxybetulinic acid, maslinic acid, α-amyrin and β-amyrin) were identified as responsible compounds for the α-glucosidase inhibitory activity. Meanwhile phenolic (rosmarinic acid), methoxy flavonoid (eupatorin, sinensetin, 5-hydroxy-6,7,3’,4’-tetramethoxyflavone, salvigenin, 6-hydroxy-5,7,3’-trimethoxyflavone and 5,6,7,3’-tetramethoxy-4’-hydroxy-8-C-prenylflavone), diterpenes (orthosiphols, orthoarisins, neoortho-siphols, staminols, and staminolactones) and triterpenes (ursolic acid, oleanolic acid, betulinic acid, hydroxybetulinic acid, maslinic acid, α-amyrin and β-amyrin) were identified  as responsible compounds for the antioxidant activity.